[OA261] Validation of probabilistic tracking method in the reconstruction of thalamocortical and optical radiation tracts: Comparison between reconstructed tracts and evoked potential recorded in epiletic patients. (August 2018) - Nici, Stefania; Artuso, Emanuele; Lizio, Domenico; Berta, Luca; Rizzi, Michele; Sartori, Ivana; Colombo, Paola Enrica; Torresin, Alberto
Abstract : Purpose: The aim of this study is to evaluate the accuracy of the probabilistic tracking method of diffusion tensor imaging fiber tractography (DTI-FT), comparing to imaging-represented electrophysiology data in epileptic patients who underwent stereoelectroncephalography (SEEG). Methods: Fourteen epileptic patients (mean age 28  ±  9), who underwent DTI acquisition and other brain MR sequences used for SEEG plannig, were selected from "Claudio Munari" Epilepsy Surgery Center database. DTI sequences were collected using a 1.5T Philips Achieva scanner by using echo planar imaging and a receive coil head SENSE 8 channels. According to the implanted electrodes position, we recorded intracerebral tibial and median somatosensory-evoked potentials (SEP) in 7 patients and flash-visual evoked potential (VEP) in 8. The thalamocortical (THC) (separately considered as median and tibial THC) and optical radiation (OR) tracts were blindly reconstructed using a probabilistic algorithm implemented in FSL 5.0.6. The tracts' reconstruction was obtained using two ROIs corresponding to a seed-point and to a way-point. The seed-point represents the starting region of the reconstructed tract, while the way-point is a region that is crossed by the reconstructed tract. In the reconstruction of THC bundle, we used the sensory thalamus as seed-point and the white matter (WM) lying underneath the somatosensory cortex as way-point. In the OR's reconstruction we used the lateral geniculate body as seed-point and the WM lying next to the calcarine cortex as way-point. The 3D tractographies were then compared to the position of SEEG electrodes contacts, on which evoked potentials (EPs) were recorded. Results: Comparison between DTI-FT and EPs showed a satisfactory superimposition of the neurophysiological recording contacts and the reconstructed tracts. We obtained full superimposition in all median thalamocortical tracts. We observed a correspondence in 81% of tibial THC and in 81% of OR, considering a maximum distance of 3mm from the tract and the neurophysiological contact. In particular, we had full correspondence in 52% of tibial THC and 70% of OR. Conclusions: This study is a preliminary one, suggesting that EPs recorded during SEEG monitoring can be considered as a valuable tool to validate the probabilistic tracking method in the reconstruction of THC and OR tracts.